Portable multi-parameter electrical impedance tomography for sleep apnea and hypoventilation monitoring: feasibility study - Lee, Min Hyoung; Jang, Geuk Young; Kim, Young Eun; Yoo, Pil Joong; Wi, Hun; Oh, Tong In; Woo, Eung Je (Physiological measurement, 2018)
Objective: Quantitative ventilation monitoring and respiratory event detection are needed for the diagnosis of sleep apnea and hypoventilation. We developed a portable device with a chest belt, nasal cannula and finger sensor to continuously acquire multi-channel signals including tidal volume, nasal pressure, respiratory effort, body position, snoring sound, ECG and SpO2. The unique feature of the device is the continuous tidal volume signal obtained from real-time lung ventilation images produced by the electrical impedance tomography (EIT) technique. Approach: The chest belt includes 16 electrodes for real-time time-difference EIT imaging and ECG data acquisitions. It also includes a microphone, accelerometer, gyroscope, magnetometer and pressure sensor to acquire, respectively, snoring sound, respiratory effort, body position and nasal pressure signals. A separate finger sensor is used to measure SpO2. The minute ventilation signal is derived from the tidal volume signal and respiration rate. Main results: The experimental results from a conductivity phantom, four swine subjects and one human volunteer show that the developed multi-parameter EIT device could supplement existing polysomnography (PSG) and home sleep test (HST) devices to improve the accuracy of sleep apnea diagnosis. The portable device could be also used as a new tool for continuous hypoventilation monitoring of non-intubated patients with respiratory depression. Significance: Following the feasibility study in this paper, future validation studies in comparison with in-lab PSG, HST and end-tidal CO2 devices are suggested to find its clinical efficacy as a sleep apnea diagnosis and hypoventilation monitoring tool.